Optimizing planar micro-transformer performance - Tahar Alili; Fatima Zohra Medjaoui; Azzedine Hamid; Abderahim Mokhefi; Yacine Guettaf; Hocine Guentri (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2026)
Faced with new requirements for isolated switching power supplies with high efficiency and power density, planar transformer technology has emerged as a serious alternative to wound components. The work presented in this paper addresses the issue of developing planar transformers in the context of low-power electronics, where volume and weight constraints are paramount. The flat shape of the coils and the interlacing of the windings do not allow for control of magneto-thermal phenomena. Although scientific literature offers numerous simulation tools to aid in the design of such transformers, it must be noted that they do not allow for a rigorous account of these phenomena. In this paper, methods and a geometric and electrical sizing tool in planar technology are used for the design of flyback direct current to direct current (DC/DC) converters. Methods for dimensioning and estimating temperature rise are presented and compared in order to develop calculation tools for design purposes. This study enabled us to observe the distribution of the magnetic field, the role of ferrite, the distribution of currents and voltages in the coils, and the distribution of temperature in our device. It should be noted that conductive and convective heat transfer processes were considered in steady state.